Proposta de um modelo de avaliação do desempenho da gestão de energia em Instituições de Ensino Superior (IES) - Fernandes, Marcio Luiz (2017)
Higher education institutions (HEIs) are inserted in an environment where sustainability aspects are strategic factors for the integration of dimensions of governance interest. It is a dynamic environment where service operations are closely linked to economic, social and environmental issues, the control and monitoring of these actions, bring important contributions to the improvement of sustainable performance and can represent a strategic opportunity for institutional development. In this way, there is a need for models that can evaluate the relation of HEIs’ activities considering environmental performance, such as energy consumption that is an essential input in the development of teaching activities. In this context, the present research seeks to propose an applied performance evaluation model, based on indicators that represent the criteria of importance in the decision-making context of energy management in HEI. In order to meet the proposed goal, a systematic review of the scientific literature on energy management performance evaluation in HEI was carried out, which allowed the identification of the evaluation context and the established reference criteria. Through a case study that used the Methodology Multicriteria Decision Aid - Constructivist (MCDA-C) as an intervention instrument, the model of HEI energy management performance evaluation was constructed, which resulted in 47 criteria establishing the measurement indicators distributed in three large dimensions (economic, facilities and socio-environmental). Seeking to determine the relevance of these criteria and the identification of new evidences for the improvement of the model, a refinement analysis was developed through the application of the Delphi technique to the specialists, connected with the confrontation of contexts through a multiple case study using the MCDA-C methodology. The results obtained accredit the set of criteria to be applied as evaluation and planning components of energy management actions in the context of HEI, allowing a systemic and integrated view that considers the different dimensions of service operations. The composition of the criteria answers different perspectives and can be treated in a strategic way, giving managers the ability to plan, monitor and evaluate the performance of energy management actions.